Mixed growth of Salix species can promote phosphate-solubilizing bacteria in the roots and rhizosphere - Koczorski, Piotr; Furtado, Bliss Ursula; Gołębiewski, Marcin; Hulisz, Piotr; Thiem, Dominika; Baum, Christel; Weih, Martin; Hrynkiewicz, Katarzyna (Frontiers in Microbiology, 2022)
Phosphorus (P) is an essential plant nutrient that can limit plant growth due to low availability in the soil. P-solubilizing bacteria in the roots and rhizosphere increase the P use efficiency of plants. This study addressed the impact of plant species, the level of plant association with bacteria (rhizosphere or root endophyte) and environmental factors (e.g., seasons, soil properties) on the abundance and diversity of P-solubilizing bacteria in short rotation coppices (SRC) of willows ( Salix spp.) for biomass production. Two willow species (S. dasyclados cv. Loden and S. schwerinii × S. viminalis cv. Tora) grown in mono- and mixed culture plots were examined for the abundance and diversity of bacteria in the root endosphere and rhizosphere during two seasons (fall and spring) in central Sweden and northern Germany. Soil properties, such as pH and available P and N, had a significant effect on the structure of the bacterial community. Microbiome analysis and culture-based methods revealed a higher diversity of rhizospheric bacteria than endophytic bacteria. The P-solubilizing bacterial isolates belonged mainly to Proteobacteria (85%), Actinobacteria (6%) and Firmicutes (9%). Pseudomonas was the most frequently isolated cultivable bacterial genus from both the root endosphere and the rhizosphere. The remaining cultivable bacterial isolates belonged to the phyla Actinobacteria and Firmicutes. In conclusion, site-specific soil conditions and the level of plant association with bacteria were the main factors shaping the bacterial communities in the willow SRCs. In particular, the concentration of available P along with the total nitrogen in the soil controlled the total bacterial diversity in willow SRCs. A lower number of endophytic and rhizospheric bacteria was observed in Loden willow species compared to that of Tora and the mix of the two, indicating that mixed growth of Salix species promotes P solubilizing bacterial diversity and abundance. Therefore, a mixed plant design was presented as a management option to increase the P availability for Salix in SRCs. This design should be tested for further species mixtures.